Como nascem os sonhos de jovens em desvantagem social? - Soares, Daniela Alves [UNESP] (UNESP - Universidade Estadual Paulista, Pró-Reitoria de Pesquisa; Programa de Pós-Graduação em Educação Matemática, 2025)
This paper was created based on data production with Brazilian and Colombian adolescent students, with the aim of proposing a typology of dreams. The construction of this typology was grounded in the analysis of confluences between dreams presented by students during interviews, their contexts, and theoretical discussion, and it is inspired by theoretical references from the field of critical education and philosophy and expands in other directions. It is also based on common characteristics present in the students' life history, as well as the characteristics of their dreams. In this typology, dreams are divided into dream as a necessity, dream as an opportunity, dream as alterity and dream as fruition. The text develops the argument that these types of dreams are one of the foundations of what is understood as motives for learning and that this can be an important reflection of understanding how dreams manifest themselves in the school environment and in mathematics classes. Discussions are also held regarding young people at a social disadvantage in the Latin American context and their role relegated to not being, in the traditionally white-Eurocentric philosophy.

Neste artigo, construído a partir da produção de dados com estudantes adolescentes brasileiros e colombianos, propõe-se uma tipologia de sonhos. A construção dessa tipologia teve por base a análise de confluências entre os sonhos apresentados pelos estudantes durante entrevistas, seus contextos e discussão teórica, e é inspirada em referenciais teóricos do campo da educação crítica e da filosofia, e se expande em outras direções. Ela se fundamenta, também, nas características em comum presentes nas histórias de vida dos estudantes, assim como nas características dos seus sonhos. Nessa tipologia, os sonhos são divididos em sonho como necessidade, sonho como oportunidade, sonho como alteridade e sonho como fruição. Desenvolve-se, no texto, o argumento de que esses tipos de sonhos se referem a um dos fundamentos do que se entende por motivos para aprender, e que esses motivos podem ser importantes para entender como os sonhos se manifestam no ambiente escolar e nas aulas de matemática. Também, são realizadas discussões a respeito do jovem em desvantagem social no contexto latino-americano e seu papel relegado a não ser, na filosofia tradicionalmente branco-eurocêntrica.
Where dreams are born of socially disadvantaged young people
Keywords: Dreams; Typology of dreams; Foreground; Teenagers; Motives for learning; Sonhos; Tipologia de sonhos; Foreground; Adolescentes; Motivos para aprender